Convective-thermal drying simulation to reduce the damage of the grain in convective plants - Dmytruk, Anatolii; Gayvas, Bogdana (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
A physical-mathematical model is proposed to analyze the process of drying the bed of one-type granular materials in a convective drying chamber under the action of a drying agent to optimize this process and reduce the percentage of grain damage. The fundamental relations of the coupled problems of mechano-diffusion and mass transfer for the considered grain are written, considering the grain structure's heterogeneity (core and coat) and its position in the bed. The moisture concentration and the radial displacement vector are chosen as determining functions. Based on the obtained solutions of changes in moisture concentration in grain over time, taking into account the heterogeneity of the grain structure and the rate of blowing the drying agent for the intergranular medium, a numerical analysis of changes in moisture concentration, temperature, displacements and deformations in grain over time is carried out, taking into account the physical and chemical characteristics of the grain. It is found that the temperature of the drying agent has the most significant influence on drying (movement, deformation, grain stress).